2020
DOI: 10.1021/acsapm.0c00196
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Sour Mixed-Gas Permeation Properties of Fluorinated Polyazole-Based Membranes

Abstract: A polyoxadiazole polymer POz-CF 3 was prepared, and complete gas permeation properties were investigated on its corresponding membrane using pure-, and multicomponent mixed-gas feeds. The POz-CF 3 membrane demonstrated attractive pureand sweet mixed-gas permeation properties; however, the performance of its membrane declined dramatically during sour mixed-gas testing. The modification of POz-CF 3 into its corresponding polytriazole polymers led to changes in their membranes' mechanical, thermal, processability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Moreover, the size, solubility, and weight of the gas molecules also have a signicant inuence on their permeation. [44][45][46] Thus, gas permeation in polymer is a very complex phenomenon, and there is rarely a simple linear relation between the gas permeability and a given parameter. [44][45][46]90 We found that there is no linear relation between the free volumes and the gas permeability for the PEI/RGO composite lms.…”
Section: Permeation Of Gas Molecules Within Rgo/pei Composite Lms In...mentioning
confidence: 99%
See 2 more Smart Citations
“…[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Moreover, the size, solubility, and weight of the gas molecules also have a signicant inuence on their permeation. [44][45][46] Thus, gas permeation in polymer is a very complex phenomenon, and there is rarely a simple linear relation between the gas permeability and a given parameter. [44][45][46]90 We found that there is no linear relation between the free volumes and the gas permeability for the PEI/RGO composite lms.…”
Section: Permeation Of Gas Molecules Within Rgo/pei Composite Lms In...mentioning
confidence: 99%
“…[44][45][46] Thus, gas permeation in polymer is a very complex phenomenon, and there is rarely a simple linear relation between the gas permeability and a given parameter. [44][45][46]90 We found that there is no linear relation between the free volumes and the gas permeability for the PEI/RGO composite lms. Nevertheless, the PALS results strongly suggest that the decrease in free volume size has made a signicant contribution to the excellent gas barrier property of the PEI/RGO composite lms.…”
Section: Permeation Of Gas Molecules Within Rgo/pei Composite Lms In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional polymers are new materials that emerged after polymer materials entered the fields of biology, energy, and electronics. The so-called "functional" means that such polymers have chemical reactivity, electrical conductivity, catalysis, biocompatibility, selective separation, energy conversion and magnetic properties in addition to their mechanical properties [10][11]. Functional polymers are widely used in medicine, environmental protection and other fields due to their advantages of light weight, high strength, corrosion resistance, diverse varieties, abundant raw materials, and simple molecular structure [12][13].…”
Section: Features Of Functional Polymer Materialsmentioning
confidence: 99%
“…Several classes of polymers have been used for gas separation. Among them, polyimides (PIs) based on 4,4 -(hexafluoroisopropylidene) diphthalic anhydride (6FDA) are emerging for various applications and are the most common used polymeric membranes due to their thermal stability, self-standing, acid resistance, and CO 2 affinity [3][4][5][6]. However, PIs with higher selectivity generally have lower permeability and vice versa [7], which was first proposed by Robeson [8] and named as "trade-off" relationship [9].…”
Section: Introductionmentioning
confidence: 99%